Phosphorus fertilization and growth of buffel grass (Cenchrus ciliares L.) cultivars - Vanderlise Giongo; Alessandra M. Salviano; Betina R. C. dos Santos; Emylly F. Leal (Revista Brasileira de Engenharia Agrícola e Ambiental)
Phosphorus (P) plays an important role in the growth of root system as well as the tillering grass, being fundamental to increase the productivity of these species. The aim of this study was to evaluate the development of buffel grass cultivars and establish critical values of P in plant and soil. The experimental set up was a 4 x 5 factorial scheme (four Cenchrus ciliaris cvs.: Biloela, Aridus, CPATSA 7754 and Pusa Giant, and five doses of P2O5 - 0, 30, 60, 90 and 120 kg ha-1) with four replications. After 90 days of cultivation, dry mass of shoot (DMS) and root (DMR) production and the P accumulation (Pacc) were determined. Soil samples to determine the P content and determination of the critical level (CriLev) were also collected. The cv. Biloela presented lower DMR and DMS production compared to the other cultivars. The cultivares Biloela, Pusa Giant and Aridus showed different critical levels of P in soil and plant, obtained in the greenhouse showing that they have different requirement of this nutrient for their growth. The cultivar CPATSA 7754 showed higher phosphorus requirement and did not permit to establish critical levels with doses used in the present study.